Reasoning and planning of therapeutic occupation activities - Dias, Carlos Manuel de Melo (2016)
Background Psychosocial rehabilitation offers the patient the opportunity to reach the maximum potential for functioning in community while performing physical, emotional and intellectual skills. Therapeutic Occupation Activities are systematic activities which structure and guide the participant's functional performance, within the interpersonal nurse-client relationship, and empowering for autonomy and promoting satisfaction and accomplishment in both occupation and recreation. Aim To explore the reasoning and planning underlying the Therapeutic Occupation Activities (TOAs) in Mental Health and Psychiatric Nursing. Methods Using a concept-based design, the methodological step-by-step framework to build the reasoning and planning underlying the Targeted Nursing Interventions (TNI) on TOAs will be described. Conclusion The clinical reasoning in Nursing allows for an updated, adaptive, sensitive and constructive decision-making. The various domains in which the TOAs are developed reveal the holistic nature of the intervention and the impact of Nursing in the individuals' life and health. The preservation of the optimal well-being and the prevention of relapses and long hospital stays are extremes of therapeutic indications which expand the philosophies of care and lead to achievable benefits, such as the feeling of social utility and the building up of self-esteem and self-image of those involved. The implications for clinical practice derive from the association between social functioning and personal satisfaction, positive and corrective reinforcement in performance, and from consistency and proportionality of modeling, assertiveness and generalization. The use of clinical indicators consistent with and sensitive to the Nurse's intervention has a clinical influence on the participants' performance and outcomes.